2010
DOI: 10.5194/acp-10-4133-2010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of marine cloud albedo via controlled sea spray injections: a global model study of the influence of emission rates, microphysics and transport

Abstract: Abstract. Modification of cloud albedo by controlled emission of sea spray particles into the atmosphere has been suggested as a possible geoengineering option to slow global warming. Previous global studies have imposed changes in cloud drop concentration in low level clouds to explore the radiative and climatic effects. Here, we use a global aerosol transport model to quantify how an imposed flux of sea spray particles affects the natural aerosol processes, the particle size distribution, and concentrations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 42 publications
7
112
2
Order By: Relevance
“…The size of the injected particles in this study is in the same size range as most previous ESM studies on sea spray climate engineering that simulate the aerosol injection (e.g. Alterskjaer et al, 2012Jones and Haywood, 2012;Korhonen et al, 2010;Muri et al, 2015;and Wang et al, 2011). It should also be mentioned that extensive measurements show that organics contribute substantially to the composition of sea spray aerosol, and in many areas is even the dominant constituent (e.g.…”
Section: Methodsmentioning
confidence: 48%
See 1 more Smart Citation
“…The size of the injected particles in this study is in the same size range as most previous ESM studies on sea spray climate engineering that simulate the aerosol injection (e.g. Alterskjaer et al, 2012Jones and Haywood, 2012;Korhonen et al, 2010;Muri et al, 2015;and Wang et al, 2011). It should also be mentioned that extensive measurements show that organics contribute substantially to the composition of sea spray aerosol, and in many areas is even the dominant constituent (e.g.…”
Section: Methodsmentioning
confidence: 48%
“…One of the advantages of simulating sea spray climate engineering in ESMs through sea salt aerosol emissions, compared to just increasing the CDNC, is that the cloud droplet activation process is taken into account. Previous studies have shown that injection of sea spray particles in some circumstances may actually reduce the CDNC due to increased competition for water vapour and reduced activation of background aerosol particles (Korhonen et al, 2010;Alterskjaer et al, 2012). showed in a single-model study that while the injection of accumulation-mode particles increased the CDNC, the injections of Aitken-or coarse-mode particles could have the opposite effect with a reduction in CDNC.…”
Section: Change In Sea Salt Concentrations Cloud Properties and Atmmentioning
confidence: 96%
“…perpendicular to the wind direction as suggested by Salter et al [7]. The vessel emits particles of 300 nm dry diameter [14,15], 25 m above the sea surface [7], at a rate of 15 kg s −1 (half the rate suggested by Salter et al [7]) for about 40 min and travels across the domain (4.8 km) once. From this emission rate, assuming the salinity of seawater to be 35 g kg −1 and NaCl being the sole solute, we derived a particle number flux of 1.72 × 10 16 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The recognition of the importance of sea salt nuclei in marine cloud processes has led to the interesting suggestion that global warming could be ameliorated somewhat through controlled enhancement of albedo and lifetime in low level marine clouds , in other words, geoengineering, whereby artificial floating sea spray generators are deployed in regions of persistent stratocumulus clouds. While intriguing as a geo-engineering solution to global warming, Korhonen et al (2010b), using a global model, and simulating emissions from a fleet of spray-emitting vessels in four regions of persistent stratocumulus fields found increases in cloud droplet concentration of maximum 20 %, and even a reduction was predicted in one region.…”
Section: Effects On Cloud Formation and Indirect Radiative Effectsmentioning
confidence: 99%